“Always paracetamol, they give them paracetamol for everything”: a qualitative study examining Eastern European migrants’ experiences of the UK health service - Hannah Madden; Jane Harris; Christian Blickem; Rebecca Harrison; Hannah Timpson (BMC Health Services Research, 2017)
Abstract Background The enlargement of the European Union since 2004 has led to an increase in the number of Eastern European migrants living in the UK. The health of this group is under-researched though some mixed evidence shows they are at higher risk of certain physical health conditions such as heart attacks, strokes, HIV and alcohol use and have poorer mental health. This is compounded by poor or insecure housing, low pay, isolation and prejudice. We aimed to understand the health needs and health service experiences of the Eastern European population in a town in Northern England. Methods Five semi structured one-to-one and small group interviews and five focus groups were conducted with 42 Eastern European participants between June and September 2014. The majority of participants were Polish and other participants were from Belarus, Hungary, Latvia, Russia, Slovakia and Ukraine. The data were analysed using thematic framework analysis. Results Key findings included a good understanding the UK health service structure and high registration and use of general practice/primary care services. However, overall, there were high levels of dissatisfaction, frustration and distrust in General Practitioners (GP). The majority of participants viewed the GP as unhelpful and dismissive; a barrier to secondary/acute care; reluctant to prescribe antibiotics; and that GPs too often advised them to take paracetamol (acetaminophen) and rest. Conclusions Overwhelmingly participants had strong opinions about access to primary care and the role of the general practitioners. Although the design of the UK health service was well understood, participants were unhappy with the system of GP as gatekeeper and felt it inferior to the consumer-focused health systems in their country of origin. More work is needed to promote the importance of self-care, reduce antibiotic and medication use, and to increase trust in the GP.